SAP NetWeaver portal technology [ the complete reference - Jay, Rabi (New York : McGraw-Hill, 2008)
Offers details on implementing and managing a SAP Portal, the tool that can integrate content - websites, applications, legacy systems, databases and document directories - into one accessible interface. This work covers the lifecycle of portal implementation, from planning, designing, and installing to configuring, tuning, and security
1. Portal implementation planning -- 2. Portal infrastructure design -- 3. Portal installation -- 4. Content administration -- 5. System administration -- 6. Portal troubleshooting -- 7. Portal security -- 8. Configuring system landscape directory
Includes bibliographical references (p. 715-719) and index
Keywords: Business enterprises -- Computer networks; SAP NetWeaver; Web portals -- Computer programs; Web site development